A Correlational of Attitude of the Mother With The Nutritional Status of Children Under Five - Theresia Ivana (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2017)
The vulnerable age of nutritional status are the children under five, then early detection and effective solution needed to decrease the risk of the problem on adult phase. The attitude of the mother were the identified factors that related with the nutritional status of child under five. These factor would involve the mother to support and promote the optimal nutritional status of their children. This research conducts to associate the attitude of the mother with the nutritional status in the Posyandu Kamboja RT 3; Posyandu Anggrek RT 9; Posyandu Kaca Piring RT 14, Puskesmas Alalak Selatan Banjarmasin. Quantitative research and cross sectional design used, sample with purposive sampling tehnique as much 97 respondents. Data collected used questionnaire, observation sheet, weight scale and microtoice. Analyse by Spearman Rank Correlation. Result: The attitude of the mother was positive (53,6%). Nutritional status of the children under five W/A was normal (63,6%), H/A normal (61,9%) and W/H normal (76,3%). There were significant correlation of the attitude of the mother with the nutritional status of children under five (Ï = 0,000).Keywords: attitude; nutritional status; mother; children under five.189